PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII - Chintya Tifani (Departemen Matematika, 2018)
Mathematical communication ability is one of learning outcome in mathematics which was expected to be mastered by students is learning mathematics. However, in fact it was students mathematical communication ability in grade VIII SMP Adabiah Padang was still low. One of learning models to improve students mathematical communication ability was by applying cooperative learning model think air share (TPS) type in the process of learning mathematics. Aim of this research is to describe whether the cooperative learning model think air share (TPS) type is better than students who learn with conventional learning. Type of research is quasi experiment with static group design. Based on data analysis using t test, it can be concluded that students mathematical communication ability who learn by applying cooperative learning model TPS type is better than students who learn with conventional learning in grade VIII SMP Adabiah Padang. Kewords conventional learning mathematical communication ability think air share model.